Understanding parental involvement in supporting early childhood talents and interests - Tri Annisa Yuli Kartika Dewi; Ega Asnatasia Maharani (Universitas Ahmad Dahlan, 2025)
Many parents still assume that a child's intelligence is limited to academic aspects, causing non-academic potential to often be overlooked. A preliminary study showed that two out of five parents were unaware of their child's talents and interests, indicating a gap in parental support. Therefore, this research aims to identify the roles of parents in developing the talents and interests of 5-to-6-year-old children in Bantul Regency, Special Region of Yogyakarta. This study employed a descriptive qualitative method with five parent respondents whose children have achievements corresponding to their talents. Data were collected through interviews and observations, and then analyzed thematically. The main findings show that parents play crucial roles encompassing five forms: introducing, managing, facilitating, supporting, and directing the child. However, this process faced obstacles such as limited practice time, insufficient supervision from working parents, and the child's unpredictable moods. These findings enrich the discourse on parental involvement in early childhood education by emphasizing the importance of parental facilitation in developing children's talents and interests.